Evaluation of root-knot nematode disease control and plant growth promotion potential of biofertilizer Ning shield on Trichosanthes kirilowii in the field - Jiang,Chun-Hao (2018)
Abstract Biofertilizer Ning shield was composed of different strains of plant growth promotion bacteria. In this study, the plant growth promotion and root-knot nematode disease control potential on Trichosanthes kirilowii in the field were evaluated. The application of Ning shield significantly reduced the diseases severity caused by Meloidogyne incognita, the biocontrol efficacy could reached up to 51.08%. Ning shield could also promote the growth of T. kirilowii in the field by increasing seedling emergence, height and the root weight. The results showed that the Ning shield could enhance the production yield up to 36.26%. Ning shield could also promote the plant growth by increasing the contents of available nitrogen, phosphorus, potassium and organic matter, and increasing the contents of leaf chlorophyll and carotenoid pigment. Moreover, Ning shield could efficiently enhance the medicinal compositions of Trichosanthes, referring to the polysaccharides and trichosanthin. Therefore, Ning shield is a promising biofertilizer, which can offer beneficial effects to T. kirilowii growers, including the plant growth promotion, the biological control of root-knot disease and enhancement of the yield and the medicinal quality.